2021
DOI: 10.1186/s13023-021-01880-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mucopolysaccharidoses (MPS) in United States: challenges and opportunities

Abstract: Background Mucopolysaccharidoses (MPS) are rare, inherited lysosomal storage disorders characterized by progressive multiorgan involvement. Previous studies on incidence and prevalence of MPS mainly focused on countries other than the United States (US), showing considerable variation by country. This study aimed to identify MPS incidence and prevalence in the US at a national and state level to guide clinicians and policy makers. Methods This retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Newborn screening has become available for MPS, but only in a few countries (52,53) and it does not remain without flaws, such as false positives / negatives resulting in misdiagnosis (53). The limited availability and affordability of these tests remains a concern in developing countries.…”
Section: Early Diagnosismentioning
confidence: 99%
“…Newborn screening has become available for MPS, but only in a few countries (52,53) and it does not remain without flaws, such as false positives / negatives resulting in misdiagnosis (53). The limited availability and affordability of these tests remains a concern in developing countries.…”
Section: Early Diagnosismentioning
confidence: 99%
“…MPSs are all autosomal recessive disorders, with the exception of MPS type II. American epidemiological studies identified the MPS prevalence rate in approximately 1:100,000 live births in the United States [ 67 ]. ERT and hematopoietic stem cell transplantation (HSCT) have been offered as treatments for MPS (muco3), limited by high cost and need for weekly injections.…”
Section: Mucopolysaccharidosismentioning
confidence: 99%
“…Table 2 summarizes the prevalence of MPS in various countries per 100,000 live births. MPS is a rare disease with the prevalence ranging from 0.00071 for MPS III in the United States to 1.89 in the Netherlands per 100,000 live births [ 21 , 22 ]. Additionally, some subtypes of MPS such as MPS IX are so rare that data were either unable to be collected or no cases were reported (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%